Pembelajaran Akidah Akhlak Berwawasan Peduli Lingkungan di MAN 1 Lamongan - Saifuddin Saifuddin (Universitas Islam Lamongan, 2019)
In this study the researchers raised the problem of increasing the character of caring for the environment by implementing Akidah Akhlak learning for students of MAN 1 Lamongan, in this study, several things will be examined, namely 1) the objectives of learning Akidah Akhlak in improving the character of caring for the environment? 2) the process of learning Akidah Akhlak in enhancing the character of caring for the environment? 3) Resources for improving the character of environmental care? Researchers use qualitative methods and a case study approach. The results of this study indicate that learning Akidah Akhlak has a role and purpose of improving the character of caring for the environment. Second, the two subjects of Akidah Akhlak in enhancing the character of caring for the environment are articulated using methods, media and strategies. Third, the resources used in the Akidah Akhlak learning process in improving the character of caring for the environment, among others, are through human resources, teaching materials, media and activities that occur in the learning process. Thus this researcher found that learning Akidah Akhlak could increase understanding and concern for the environment.